Effects of Carboxymethylation on the gelling properties of kappa-carrageenan-long bean gum mixture. - Fabie, Julienne Stephanie B.
This work presents the effects of carboxymethylation on the gelling properties of kappa-carrageenan-Long Bean gum (k-carr-G) mixture. Long Bean gum as used herein refers to the galactomannan extracted from Vigna unguiculata. Two sets of binary mixtures made up of k-carr and galactomannans were prepared. GThe first set contained the noncarboxymethylated galactomannan (k-carr-G) while the other set contained the carboxymethylated galactomannan (k-carr-CMG). Each binary mixture contained 1.5 percent k-carr and six different galactomannan concentrations (0percent, 0.1percent, 0.25percent, 0.75percent, 1.0percent). The gelling properties were gelling and melting temperatures, syneresis index, gel strength, and viscosity. Analysis of variance (ANOVA) at a=0.10 showed that the gelling temperature and syneresis index were decreased with carboxymethylation while melting temperature and gel strength were increased. The result on viscosity using the given set of galactomannans concentrations, however, was inconclusive. The presence of a sharp peak at 1664 cm raised to negative 1 in the FTIR spectrum of k-carr-CMG confirmed the success of carboxymethylation on the galactomannan.